Increasing Professional Competencies in Students of Pedagogical Universities - Mamlakat Azadovna Ruzmetova (Euro Asian Journal Publishing, 2023)
In this article we are talking about a pedagogical experiment, using the questionnaire method, conducted by us in 3 pedagogical universities of Uzbekistan, in order to check the availability of professional competencies of 3rd - 4th year students of the direction: "Physics and Astronomy". The purpose, objectives of the pedagogical experiment and its conclusions are described
Keywords: Pedagogical experiment; questionnaire; professional competencies